Does Income Smoothing Improve Earnings Informativeness? - Tucker, Jennifer W.; Zarowin, Paul A. (The Accounting Review, 2006)
This paper uses a new approach to examine whether income smoothing garbles earnings information or improves the informativeness of past and current earnings about future earnings and cash flows. We measure income smoothing by the negative correlation of a firm's change in discretionary accruals with its change in premanaged earnings. Using the approach of Collins et al. (1994), we find that the change in the current stock price of higher-smoothing firms contains more information about their future earnings than does the change in the stock price of lower-smoothing firms. This result is robust to decomposing earnings into cash flows and accruals and to controlling for firm size, growth, future earnings variability, private information search activities, and cross-sectional correlations.